IMBAS MUSIK ETNIK ISLAM NUSANTAR PADA ERA GLOBALISASI DI PROVINSI MALUKU - Syarifudin Syarifudin (Jurnal Studi Islam, 2021)
This research is related to ethnic Islamic music of the archipelago in the midst of the globalization impact of LASQI in Maluku province. The problem of this study is how the impact of modern ethnic music on ethnic music in Maluku, especially qasidah, hadrat, and sawat at the Qasidah Art Institute of Maluku Province (LASQI). This type of research is descriptive qualitative. The research location is at the Indonesian Qasidah Art Institute, Maluku province. Data collection techniques used the FGD method and in-depth interviews with the Maluku Province LASQI Management and practitioners of ethnic music in Maluku. This study finds that Maluku ethnic music is threatened with extinction and the impact of modern music has dominated the life trends of young people in Maluku, so it is predicted that the existence of ethnic music in Maluku will decrease and change its essence. The impact of global culture on the challenges of Nusantara Islamic ethnic music at LASQI Maluku Province can be seen in all-electric musical instruments. The impact of Western music on the development of the ethnic music industry is dominated by the aspect of music equipment, the insight of music practitioners, and aspects of psychological expression that do not provide enlightenment to the heart as the legacy of the ancestors who used music as a ritual medium to marvel at Allah swt. by singing, reading sholawat as a compliment to the Messenger of Allah. The method of preserving the ethnic Islamic music of the Nusantara LASQI Maluku Province by increasing the strengthening of sharia intelligence; Improving the quality of music technology, and increasing entrepreneurship. Members of music practitioners in Maluku as a force to prevent the domination of modern music by programming ethnic music, sahur music, and collaboration between ethnic and modern music.